2016
DOI: 10.1007/s10876-016-1123-7
|View full text |Cite
|
Sign up to set email alerts
|

Green-Synthesis of Selenium Nanoparticles Using Garlic Cloves (Allium sativum): Biophysical Characterization and Cytotoxicity on Vero Cells

Abstract: Nanotechnology has the potential to revolutionize a number of research fields, including biomedicine. Currently, the fabrication of biocompatible nanomaterials is of high interest worldwide. Little is known about the possible synthetic routes to fabricate selenium nanoparticles. In this research, we focused on the potential of a medicinally important plant species, garlic (Allium sativum), for the green synthesis of selenium nanoparticles. The garlic aqueous extracts acted as a capping and reducing agent in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 55 publications
14
70
0
Order By: Relevance
“…No appreciable decline in cell viability was observed at the tested concentrations (including MIC values), portraying their safety profile for antibacterial application [23,44].…”
Section: Biocompatibilitymentioning
confidence: 78%
See 2 more Smart Citations
“…No appreciable decline in cell viability was observed at the tested concentrations (including MIC values), portraying their safety profile for antibacterial application [23,44].…”
Section: Biocompatibilitymentioning
confidence: 78%
“…The UV-vis spectra of the resulting nSe revealed a sharp characteristic peak at 272 nm, while no such peaks were observed in the absorption spectra of extract and Na 2 SeO 3 solution (figure 2). The appearance of colour and subsequent absorption peak of nSe was attributed to the surface plasmon resonance (SPR) phenomenon [30,44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported literature studies revealed that, Na 2 SeO 3 solution (10 mM) was prepared by addition of 0.263 g of its salt into the 100 mL of DI water [2,4,17,18]. In typical synthesis, different amounts (1-5 mL) of ALE were mixed with various amounts (10-30 mL) of Na 2 SeO 3 solution.…”
Section: Fabrication Of the Se Nps Using Alementioning
confidence: 99%
“…Red colour of the reaction mixture solution indicates that the Se NPs by reduction of the Se ions and converting them to the elemental Se and formation of the Se NPs [21]. Several studies indicated that by synthesis of the Se NPs in the solution, its colour progressively varies from the dark yellow into the red [17,22]. The colour intensity of the colloidal solution containing synthesized Se NPs was measured using UV-Vis spectrophotometry adjusted at 420 nm (wavelength) and stated as absorbance unit (% a.u.…”
Section: Colour Intensity Of the Synthesized Se Npsmentioning
confidence: 99%